Graphing Calculators and Their Effect on Students' Understanding of Functions - Williams, Dolores (Valdosta State University, 2006)
Scientific graphing technology offers teaching and learning aids currently utilized mainly by teachers and students in upper-level mathematics classes. In this study, a class of ninth-grade Algebra I students possessing only basic scientific calculator experience used scientific graphing calculators to aid in graphing linear equations and inequalities. Results from the study confirmed that the students' use of graphing calculators positively influenced their ability to graph and identify graphs of linear equations. Students who scored higher on the pretest, indicating stronger initial graphing skills, tended to use the calculator to check their work. Students who did not score well on the pretest tended to use the calculator to graph the equation and then copy the results onto their graph paper. Overall, students confirmed that they were more comfortable with using the graphing calculator after the intervention. Previous studies had shown that graphing calculators were viable tools for higher level mathematics classes in high school. This study presented evidence that this tool was just as beneficial for ninth-graders taking Algebra I.
Keywords: graphing technology; Algebra; linear equations; Educational technology; Teaching--Aids and devices; Computer-assisted instruction